Retrospective study for the results of proximal femoral nailing in subtrochanteric fractures - Mandalia, Manthan H.; Kubavat, Hasmukh L.; Trivedi, Nirav (International Journal of Research in Orthopaedics, 2020)
Background: Subtrochanteric fractures are prevalent in young and old age groups and one of the most notorious to achieve a stable fixation which allows early union and mobilization. This was a retrospective study to analyse the outcomes of proximal femur nailing in subtrochanteric fractures and assess the functional outcome, radiological union and compare that with studies of other modalities. Methods: This was a retrospective study of 40 patients with sub trochanteric fractures classified by Sienshiemer classification and operated by proximal femoral nail implant. Clinical evaluation was done by Harris hip score. Results: The average union time in our study was 5.12 months lower than some of the union rates of series with other implants (AO blade plate 7.7%). The conducive environment provided by proximal femoral nail (PFN) allows early mobility, independence to the patient and lessens the complications due to the bed ridden state and decrease the time in returning to work. Conclusions: Our study suggests that PFN being and intramedullary implant gives stable fixation and early union as compared to extramedullary implants with less blood loss and less complications.